Nuevos métodos de diagnóstico en las afecciones bacterianas intestinales - Colichón, Héctor (1956)
The latest amendments to the "SLU" means make this media play a key role in preminal and basic differentiation that is required for screening of pathogenic forms of Enterobacteriaceae in practice the diagnosis of intestinal bacterial infections. In general all Enterobacteriaceae grown in this medium can lead to three types of changes according to their physiological properties: First, crops that produce blue shift without gas. Second, making a half turn to red and; third, they do not produce any modification or change except rare gas bubbles. In these three variations all Enterobacteriaceae are grouped, the first comprising at Proteus only; the sequndo to E. coli, E. freudii, Klebsiella and Aerobacter and; the third, to Groups: Salmonella, Arizona, Providence and Shigella. Differentiation of each group within each variation is done with the help of other tests already mentioned in the preceding Tables. A method is proposed to place two media in a single petri dish, because the combination of a selective medium properties of a class with another of different selectivity, brings new observations and differential data very useful in the practice of isolation and bacteriological diagnosis. This arrangement brings a new area close to the line joining the two media where no colonies growing on selective medium of each areas may appear. When the combination is a selective medium with another non-selective. this area is an area that is convenient intermediate selectivity for the isolation of microbial pathogens which can be inhibited by the selective media. The combination of two means in one plate and the respective equivalent planting areas occupied by each medium. yields new data on the identity of the crop for comparative observation of inhibition or development.